Teaching other people's children, elsewhere, for a while: the rhetoric of a travelling educational reform. Issue 1 (2nd January 2016) - Ellis, Viv; Maguire, Meg; Trippestad, Tom Are; Liu, Yunqiu; Yang, Xiaowei; Zeichner, Kenneth
Abstract: Teach for All is a good example of a globally travelling educational reform policy. In this article, we examine the rhetoric of the reform through an analysis of its public discourse, specifically the websites for the umbrella organization, 3 of its 35 constituent projects (Teach for America, Teach First and Teach for China) and one associated project (Teach First Norway). The analysis focuses on the rhetorical production of teaching as something done to other people's children, in places apart from and outside the communities and schools of dominant populations, and for a while only – as a short-term mission rather than what is usually understood as a professional career. We argue that the principal motive underlying Teach for All's rhetoric is the cultivation of a cadre of leaders and a form of neoliberal social entrepreneurship that it claims will solve the problem of 'broken' societies, public services and, specifically, schools.